Elevating Design in the Organization. Issue 4 (10th December 2017) - Micheli, Pietro; Perks, Helen; Beverland, Michael B.
Abstract : Following evidence of its positive contribution to innovation and company performance, many firms are seeking to elevate design to a strategic level. However, little is known as to how this can be achieved. This study draws on the literatures concerned with elevating organizational functions and with organizational legitimacy, and aims to unravel and detail critical practices and potential tensions influencing the elevation of design's status in firms. To do so, 53 in‐depth interviews were undertaken with key informants, representing a range of functional specialisms, in 12 companies, including large multinational companies as well as small and medium‐sized enterprises (SMEs). Findings show how six practices—top management support, leadership of the design function, generating awareness of design's role and contribution, interfunctional coordination, evaluation of design, and formalization of product and service development processes—affect the design elevation process. In contrast with previous studies on raising the status of organizational functions, this research reveals that the same practice can play both positive and negative roles, and that there are fundamental tensions, which should be reconciled if design's status is to be elevated. Drawing on the concept of organizational legitimacy, we also examine how design moves beyond being seen as pragmatically useful, to being identified as a relevant, alternative way of operating, to being regarded as essential for success. The article concludes by articulating contributions to design and innovation management theory and practice, and to the body of scholarly work seeking to understand how to elevate the status of a function.